2014
DOI: 10.1093/infdis/jiu125
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Drive CD4+ T-Cell Cycling and Impaired Responsiveness to Interleukin 7: Implications for Immune Failure in HIV Disease

Abstract: Induction of CD4(+) T-cell turnover and diminished T-cell responsiveness to IL-7 by IL-1β and IL-6 exposure may contribute to the lack of CD4(+) T-cell reconstitution in treated HIV-infected subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 50 publications
4
86
0
Order By: Relevance
“…In earlier work, we showed that a variety of microbial TLR agonists, including bacterial LPS and single-stranded RNAs that, like HIV, can bind and signal through TLR7 and TLR8, could indirectly activate memory CD4 ϩ T cells to enter the cell cycle (20). In more recent work, we found that the inflammatory cytokines IL-6 and IL-1␤, which are inducible by these microbial products, can also drive the cycling of CD4 ϩ T cells in vitro and can block IL-7 responsiveness (34). The significance of the negative correlation between memory CD4 ϩ T cell cycling and plasma LPS levels in healthy controls is less clear.…”
Section: Discussionmentioning
confidence: 95%
“…In earlier work, we showed that a variety of microbial TLR agonists, including bacterial LPS and single-stranded RNAs that, like HIV, can bind and signal through TLR7 and TLR8, could indirectly activate memory CD4 ϩ T cells to enter the cell cycle (20). In more recent work, we found that the inflammatory cytokines IL-6 and IL-1␤, which are inducible by these microbial products, can also drive the cycling of CD4 ϩ T cells in vitro and can block IL-7 responsiveness (34). The significance of the negative correlation between memory CD4 ϩ T cell cycling and plasma LPS levels in healthy controls is less clear.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we analyzed the levels of 16 inflammatory cytokines, chemokines, and markers of gut damage and microbial translocation at or before seroconversion to assess the effect of vRC on the early inflammatory milieu [n = 33; previously dichotomized into lowand high-vRC phenotypes (15)]. We found that vRC was positively correlated with a number of inflammatory cytokines (Table 2), most notably IL-6 and IL-1β, two proinflammatory cytokines previously implicated in driving aberrant CD4 + T-cell turnover and impairing homeostatic proliferation (21). Of note, vRC was also strongly correlated with elevated levels of IL-10, an important antiinflammatory cytokine linked to T-cell dysfunction in HIV infection (22,23).…”
Section: Viral Replicative Capacity Alters Early Inflammatory Cytokinmentioning
confidence: 87%
“…Recently, we and others have reported increased levels of IL-1β in the lymphoid tissues of untreated and ART-treated HIV infected patients and have found that IL-1β can promote the expansion of memory CD4 and CD8 T cells in vitro without addition of exogenous antigen (70, 71). It is plausible that sustained expression of inflammatory cytokines such as IFN-a IL-1 β and IL-15 play a role in the profound and persistent memory CD8 T cell expansion that characterizes HIV infection.…”
Section: What Are the Determinants Of Cd8 T Cell Persistence In Treatmentioning
confidence: 94%